Using the Space Syntax Analysis to Examine the Spatial Configuration of Houses Layouts and Its Transformation over Time in Biskra City - Rihane Barkat; Yassine Bada; Yasemin İnce Güney; Hafnaoui Hamzaoui (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Urban complexity of the Algerian town, in this case the city of Biskra, consisting of a compilation of different fabrics through history (the old city, the colonial fabric, and the post-independence fabric), has produced several housing types. Therefore, a variety of domestic architecture has emerged; vernacular, colonial, self-built (independent), and contemporary houses. Houses architecture is apparently different from one type to other in organization and morphological aspect. The study based on analytical-comparative to examine the transformation of the spatial organization of a sample of houses layouts from different periods of time (pre-colonial, colonial, independence, and contemporary period) in term of permeability, in Biskra city. The aim of this study is to uncover the genotype and the underlying characteristics of different spatial layouts by using the space syntax method. This paper explores the influence of inhabitant’s behaviors and the socio-cultural effects on the spatial configuration and space-functions of the houses layouts. In the context of discovering the differentiation and the similarities between the samples that consist of 16 houses: four houses from each period; an analysis has been carried out by applying the “Gammaanalysis” using the A-graph program in detecting the genotypical consistencies in their patterning.